Global, regional, and National burden of metabolic dysfunction-associated steatohepatitis-related liver cancer in older adults: trends and cross-national inequality based on the global burden of disease study 2021 - Weikang Meng; Jingsheng Hua; Jingyu Sun; Hengfang Liu; Jie Qian; Yating Gu (Discover Oncology)
Abstract Background Understanding the temporal trends of metabolic dysfunction-associated steatohepatitis-related liver cancer (MASH-LC) in older adults is crucial for raising public awareness and informing future policy decisions. Methods This is the first study to use Global Burden of Disease (GBD) data to analyze the burden of MASH-LC specifically in adults aged 65 years and older. Utilizing data from GBD 2021, we analyzed the incidence, mortality, and disability-adjusted life years (DALYs) of MASH-LC among individuals aged 65 and older from 1990 to 2021. We also examined corresponding age-standardized rates and conducted stratified analyses based on region, sex, age, and temporal changes. To assess cross-national health inequality, we further applied the slope index of inequality (SII) and concentration index (CI), which have not been previously employed in studies of MASH-LC among older adults. Results Globally, age-standardized incidence, mortality, and DALYs rates (ASIR, ASMR, and ASDR) of MASH-LC in older adults exhibited a significant upward trend, with a higher burden observed in males. The absolute numbers of incidence, deaths, and DALYs increased by 251.59%, 231.08%, and 211.00%, respectively. While ASIR declined notably in high-sociodemographic index (SDI) regions, ASMR and ASDR were highest in low-SDI regions by 2021. China bore the heaviest burden globally, whereas Australia and the United Kingdom experienced the most substantial growth. Cross-national inequality analyses indicate that indicated that the burden of MASH-LC in older adults was more concentrated in low-SDI countries. Additionally, the disease burden escalated with age, with peak burden ages differing slightly between sexes. Conclusion The global burden of MASH-LC in older adults has risen markedly. Targeted preventive strategies are urgently needed to mitigate disease progression and reduce disparities across populations.